Ramifications of debt restructuring on the euro area: The example of large European economies' exposure to Greece - Ansgar Belke; Christian Dreger (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The Greek government budget situation plays a central role in the debt crisis in the euro area. The debt to GDP ratio is above 150 percent, while the deficit to GDP ratio exceeds 10 percent. To re-establish the Maastricht criteria, respectively, strong consolidation measures need to be implemented, with potential adverse effects on the Greek economy, and further credit requirements. Therefore, a debt conversion might become a reasonable alternative. The aim of this paper is to provide some simulation-based calculations on the expected fiscal costs for the governments in the large European countries Germany, France, Spain and Italy arising from different policy options - among them a potential second Greek rescue package. Under realistic conditions, a debt conversion may be the less costly strategy for Greece and the euro area partner states. A value-added of these calculations lies in a potential transfer to smaller euro area member countries.
Keywords: F33; F34; H63; 330; euro area debt crisis; debt conversation; Greece; Haushaltskonsolidierung; Staatsbankrott; Griechenland; Internationaler Transfer; Soziale Kosten; EU-Staaten